Does E-Service Quality and Social Network Really Matter? Examining Its Impact on Trust and Purchase Intention - I Gusti Ayu Cynthia Puspita Sari; Nilna Muna (Quantitative Economics and Management Studies, 2024)
Current study explored the connection between e-service quality, social networks, purchase intention, and customer trust, specifically focusing on how artificial intelligence impacts e-service quality within insurance companies. This research employed Theory of Planned Behavior as the basis foundation and conducted through a quantitative approach. Denpasar was used as the research location and targeting 150 local communities as respondents. Empirical data was collected through questionnaires and the analysis was performed using Structural Equation Modeling (SEM) with AMOS version 23 software. The findings indicate significant and positive relationships among all variables, leading to the acceptance of all hypothesis. The findings of this research show that the quality of AI-based services and social networks has a significant impact on the level of consumer trust in insurance products. A high level of trust in the quality of insurance products will in turn increase consumers' willingness to use these insurance products, thereby stimulating consumer loyalty towards insurance companies. The results of data analysis highlight that trust is a crucial key in consumer interest in purchasing a product. Interesting findings from this research also emphasize that gender, especially female consumers, show higher interest in insurance products. This is due to the belief that women have a high awareness of health and financial risks, thus motivating them to use insurance products.